Clinical Studies Reporting on Vascular Graft Coatings for the Prevention of Aortic Graft Infection: A Systematic Review and Meta-Analysis. (January 2022) - Mufty, Hozan; Van den Bergh, Mats; Meuris, Bart; Metsemakers, Willem-Jan; Fourneau, Inge
Abstract : Objective: The aim of this study was to investigate the efficacy of vascular graft coatings used in the aortic position to prevent vascular graft infection (VGI). Methods: A systematic review was conducted in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines using a pre-registered protocol (CRD42020206436). Eligible studies used a vascular graft coating in the aortic position and reported on VGI. A search was performed in MEDLINE (PubMed), Embase, Web of Science, and the Cochrane Library. Primary outcome parameters were VGI, patency, and mortality. Pooled estimates of VGI were calculated using odds ratio (OR) and 95% confidence intervals (CIs) wherever possible. Quality assessment was performed with the Newcastle–Ottawa Assessment Scale and the Revised Cochrane risk of bias tool for randomised trials. Results: In total, 6 873 papers were identified. Only eight studies were included. Six of eight studies (75%) reported on known antimicrobial coating strategies such as antibiotics ( n  = 3) and silver ( n  = 3). In the other two studies, polymer coated grafts were used. Only three of eight studies compared coated with uncoated grafts (two antibiotic and one silver). Two randomised controlled trials reported on the effect of rifampicin soaked (1 mg/mL) grafts and showed no significant effect in the early (2 months; OR 0.69, 95% CI 0.29 – 1.62) or late (2 years; OR 0.73, 95% CI 0.23 – 2.32) post-operative periods. A retrospective cohort study focusing on the effect of silver coated grafts did not reveal any advantage (OR 0.19, 95% CI 0.02 – 1.64). Two polymer coated grafts were not considered to have a potential benefit in the prevention of VGIs. Conclusion: Clinical studies reporting on the antibacterial effect of vascular graft coatings in the aortic position to prevent VGI are scarce. For silver and antibiotic coatings, no significant protection for VGI was observed. New types of grafts or long acting coating strategies are mandatory to prevent this complication in the future.